Adolescents' Experiences of Staying Overnight at Family-Centered Pediatric Wards - Johan Lundgren PhD, RN; Annika Norell-Clarke PhD, LCP; Ingrid Hellström PhD, RN; Charlotte Angelhoff PhD, RN (SAGE Publishing, 2020)
Background Sleep is essential for health and recovery. Hospital stays may affect adolescents' sleep quality negatively as routines in the ward are not adapted for adolescents' developmental status or sleep habits. The aims with this study were to (a) explore and describe how adolescents experience sleep in the family-centered pediatric ward, (b) explore and describe how adolescents experience the presence or absence of a parent during the hospital stay, and (c) identify circumstances that the adolescents describe as influential of their sleep in the pediatric wards. Methods This is a qualitative interview study employing thematic analysis with an inductive and exploratory approach. Sixteen adolescents aged between 13 and 17 years participated in the study. Results Three themes were found: the importance of good sleep, safety as a prerequisite for sleep in hospital, and circumstances influencing adolescents' sleep in hospital. Conclusion The adolescents described their sleep at the pediatric ward positively, but mentioned disturbing factors associated with pain, nightly check-ups, noises, and inactivity. Parental presence was perceived as very positive both during the night and the day.